Economic Factors Affecting Rice Price Fluctuation in North Sumatera - Mariana Eva Yanti; Octasella Ainani As’ad; Faiz Ahmad Sibuea (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The research approach method is a qualitative approach. The method of data collection is secondary data, secondary data needed is obtained from relevant agencies, namely from the Central Bureau of Statistics and the Department of Agriculture as well as other literature related to research. The analytical method used is descriptive analysis and analysis of Vector Auto Regression (VAR). The results showed that: 1) The dominant factors affecting rice prices in North Sumatra are 2, the first is 60% production because the higher the production of rice, the price of rice will decline and the lower the production, the price of rice will increase and the second factor is 38% inflation because if the price of rice continues to increase there will be inflation, but it is different from the fact that rice prices fluctuate due to the stability of rice prices. 2) Factors that affect rice prices in North Sumatra in the short term are significant, namely inflation and in the long term there are five significant factors, namely production (prod), harvest area (field), income (inc), consumption (cons) ) and inflation (inf). 3) From Impulse Response Function Analysis, it can be seen that the factors that influence rice prices in North Sumatra can be seen as stability, namely the production variable (Prod) reaches stability in the 25th period, the penen variable (Field) reaches stability in the period 28, the consumption variable (Cons) reaches stability in the 25th period, the income (Inc) variable reaches stability in the 20th period, the inflation variable reaches stability in the 27th period. namely inflation and in the long term there are five significant factors, namely production (prod), harvest area (field), income (inc), consumption (cons) and inflation (inf).